2002
DOI: 10.1016/s0895-7061(02)02272-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functional Na+/Mg2+ exchanger in human trophoblast cells

Abstract: The JEG-3 cells appear to possess a functional Na/Mg exchanger that functions to maintain low [Mg2+]i in cytotrophoblast cells. In addition, [Mg2+]i is acutely regulated by [Mg]o. Because placental trophoblasts are sites of maternal-fetal ion exchange, and [Mg]o is altered in preeclampsia, derangements in or modulation of this exchanger may contribute to complications of pregnancy such as pregnancy-induced hypertension, pre-eclampsia, and preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
0
21
0
3
Order By: Relevance
“…The presence of claudin 16 at the lateral plasma membrane of the syncytiotrophoblast layer is the first evidence to suggest the occurrence of paracellular transport of Mg 2+ between the maternal blood and the intercellular space of the human placenta. Of note, fetal blood has higher levels of ionized Mg 2+ in comparison with maternal blood (Standley and Standley 2002). The absence of claudin 16 immunolocalization at the placental vessels further suggests that once Mg 2+ enters the lumen of placental vessels, by an as yet undefined mechanism, the cation might not be driven out through the TJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of claudin 16 at the lateral plasma membrane of the syncytiotrophoblast layer is the first evidence to suggest the occurrence of paracellular transport of Mg 2+ between the maternal blood and the intercellular space of the human placenta. Of note, fetal blood has higher levels of ionized Mg 2+ in comparison with maternal blood (Standley and Standley 2002). The absence of claudin 16 immunolocalization at the placental vessels further suggests that once Mg 2+ enters the lumen of placental vessels, by an as yet undefined mechanism, the cation might not be driven out through the TJ.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of claudin 16 immunolocalization at the placental vessels further suggests that once Mg 2+ enters the lumen of placental vessels, by an as yet undefined mechanism, the cation might not be driven out through the TJ. With regards to Mg 2+ transport in the human placenta, only the presence of a functional Na + /Mg 2+ exchanger that maintains low intracellular Mg 2+ in choriocarcinoma JEG-3 cells in culture has been reported (Standley and Standley 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium levels in maternal blood and cord blood of infants of severe preeclamptic and healthy pregnant women were studied and the magnesium level was found to be higher in the cord blood, while it was lower in the mothers' blood [12]. The authors concluded that magnesium may play an important role in numerous biochemical processes, including a protective effect on the developing fetus' brain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Essa hipótese foi aventada devido ao efeito vasodilatador do sulfato de magnésio, já conhecido na literatura 7,8,9 . Entretanto, observou-se um aumento da freqüência de fetos com artéria cerebral média fetal alterada, possivelmente devido à afinidade cerebral do sulfato de magnésio 14 , ocasionando diminuição da resistên-cia vascular nessa artéria.…”
Section: Discussionunclassified
“…O magnésio é o mais abundante e importante cátion bivalente intracelular, responsável por diversas funções. Credita-se a este cátion o importante papel na regulação da pressão sangüínea através da modulação da reatividade do tono vascular e da resistência periférica total 7,8,9 . O aumento na concentração do magnésio extracelular resulta em vasodilatação, atenuando os agonistas que induzem a vasoconstrição.…”
Section: Introductionunclassified